First-year student aspirations: a multinodal analysis - Grellier, Jane (Routledge, 2013)
This article explores the aspirations of first-year university students in a particular socio-geographic context, by juxtaposing this context with those of Western universities in the 1970s. The rhizomatic analysis enables student voices and personal narratives to complement, extend and undercut the words of published researchers and of the university administration. As with other rhizomatic analyses, its non-linear structure, without evident beginning and ending, permits readers to begin at any point, making multiple connections between nodes. Readers create their own intertextual connections, and are encouraged to read the students’ aspirations in the context of their own undergraduate experience.